Highly-skilled weightlifters' pre-competitive training individualization technology - Khomenko, R. V.; Antropova, E. V.; Kokin, V. Y. (Theory and Practice of Physical Culture, 2017)
Objective of the study was to provide theoretical grounds for the highly-skilled weightlifters` precompetitive training individualization technology. The study was designed to build up the precompetitive training individualization technology with due consideration for the specific fitness progress phases to facilitate the highest competitive fitness being attained based on prudent management of the individual progress paths versus the actual bodily resources of the athletes, their starting performance versus current performance rates, and training loads versus training effects. Based on this approach, we developed a training process individualisation program for application at precompetitive stages. Subject to the study was a variable sample of weightlifters (n=30) fairly close in their fitness and skill levels, aged 17-24 years and qualified Candidate Masters of Sport (n=20) and Masters of Sport (n=10). As demonstrated by our study of the modern athletic training theory and practices, the precompetitive training process individualisation is a top priority in any training system focused on competitive success, with the training being duly individualized to prudently manage workloads, fitness and training conditions for the expected competitive success.